Service quality in the banking sector in an emerging economy: A consumer survey - (:unkn) unknown (My University, 1997)
Reports on the results and managerial implications of a Turkish study which investigated relationships between service quality, and customer satisfaction, complaint behaviour and commitment. Concludes that the ultimate success of any service quality programme implemented by a bank can only be gauged by creation and retention of satisfied customers. The role of customer-contact personnel in the attainment of these goals is of paramount importance. Therefore, in their efforts to deliver high quality services to their external publics (i.e. clients), banks should not ignore the specific needs of their internal publics, notably their customer-contact employees. © 1997, MCB UP Limited